EVALUASI USER EXPERIENCE APLIKASI BANK JAGO MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Muhimmatul Faizah; Eki Saputra; Megawati Megawati; Mona Fronita (Program Studi Sistem Informasi, Universitas Banten Jaya, 2026)
Digital transformation in the banking sector is essential to meet evolving customer expectations and compete with advances in financial technology (fintech). Bank Indonesia's report shows digital banking transaction growth of 34.49% year-on-year in Q2/2024, reflecting the increasing adoption of digital services. As one of the five fully digital banks in Indonesia, Bank Jago must ensure a seamless user experience to remain competitive. This study evaluates the user experience of the Bank Jago app using the User Experience Questionnaire (UEQ). The results showed that all dimensions received positive ratings, with attractiveness getting the highest score of 1,673, followed by perspicuity and stimulation. However, efficiency, dependability, and novelty received lower ratings. The comparative analysis places Bank Jago in the “Good” category for attractiveness and stimulation, “Above Average” for perspicuity and novelty, and “Below Average” for efficiency and dependability. Interview results support these findings, with users expressing concerns about system speed, security, complaint response time, and real-time notifications. Therefore, while the user experience is generally positive, focused improvements are needed to enhance usability and maintain competitiveness in the digital banking sector.